Kelayakan Usaha Budidaya Ikan Lele Dumbo (Clarias gariepinus) dan Pengaruhnya terhadap Tingkat Pendapatan Petani Ikan Lele di Kabupaten Tabanan - SUDANA, SN.; ARGA, IW.; SUPARTA, N. (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol. 1, No. 1, Mei 2013, 2014)
African catfish production in Tabanan in 2010 is not able to meet demand, so the shortcomings come from outside the regency of Tabanan, in terms of land Tabanan regency has vast untapped potential. The high demand for African catfish contains high nutrition, delicious, cheap, and easily cultivated. But the fact that the fish farmers have worked and many have failed. The purpose of this study was to determine the feasibility of financial, marketing, and social African catfish fish cultivation and its impact on catfish farmers' income. The research method used survey research approach to the analysis of quantitative and qualitative methods. Research sites in Tabanan regency. The scope of the feasibility study includes an analysis of the financial aspects, marketing, social, and its effect on catfish farmers' income. The results showed that the financial aspects of the business viable, marketing and social. The feasibility aspects of marketing have the most dominant effect on farmers' income compared to the financial and social aspects. Changes in output price are more than sensitive than the input. The need for venture capital is large enough for catfish farmers. Based on the conclusions can be suggested: (1) efforts should be developed to be able to further increase farmers' income, (2) an increase in scale effort to increase profits, implement effective technologies, increasing knowledge and skills of African catfish aquaculture, (3) respond to any trend of development output prices so did not experience greater losses, (4) Government policies need to prepare capital cheaper and easier.
Keywords: Feasibility, fish cultivation African catfish, catfish farmers' income.